comparative literature; literary translations; poetry; metaphysical poets; George Herbert - Banaszak, Michał (Porównania, 2019)
The poem Virtue by the metaphysical poet George Herbert is a challenge for its translators, especially in formal terms. The author of the article analyses four translations of this work into Polish, made in the 20th or 21st century – by Jerzy Pietrkiewicz, Jerzy S. Sito, Stanisław Barańczak and Maciej Froński. He enumerates the transformations made in relation to the original, determines their reasons and consequences, taking under consideration such factors as the translators’ creative personality, their aims and applied strategies. The results of these analyses allow to evaluate how these factors influenced the final depiction of Virtue available to Polish-language readers.